In Algorithms We Trust: Magical Thinking, Superin℡ligent Ai and Quantum Computing - Schradle, Nathan (Zygon, 2020)
This article analyzes current attitudes toward artificial intelligence (AI) and quantum computing and argues that they represent a modern-day form of magical thinking. It proposes that AI and quantum computing are thus excellent examples of the ways that traditional distinctions between religion, science, and magic fail to account for the vibrancy and energy that surround modern technologies.